Sales Force Targets and Its Psychological Effect on Job Satisfaction of Supply Chain Employees through Pressure and Stress in Indonesian Automobile Industry - Edward Markwei Martey; Yaw Brew; Joseph Frempong (International Journal of Supply Chain Management, 2020)
Objective of this study is to examine the psychological effect of sales force targets on job satisfaction of supply chain employees. Number of studies available in the literature examining the role of target among various companies, however, the sale force targets was not examined in the automobile industry. Especially, the psychological effect of sale force targets is not examined on job satisfaction. Thus, this study examined the valuable relationship between psychological effect of sale force targets, pressure, stress and job satisfaction. Population of this study is based on the automobile companies of Indonesia. The reason to select automobile companies is that; these companies are facing numerous issues related to the employees and previous studies did not consider the psychological role of sale force targets on employees. A survey was carried out and total 271 questionnaires were returned and used in the data analysis. Results of the study highlighted that psychological effect of sale force targets has significant role in employee job satisfaction of supply chain employees. Psychological effect of sale force targets has increased the pressure on employee and increases the stress which lead to the decrease in job satisfaction. Increase in employee pressure and employee stress finally decreases the job satisfaction.